Dry and breathable nursing core material and production process thereof

Through the lamination bonding and esterification reaction of cellulose acetate nanofiber membrane and modified polyvinyl alcohol nanofiber membrane, the problem of nanofiber dissolution during the moisture absorption process of traditional care core materials was solved, and a dry and breathable care core material with a significant fast-drying wet-guided gradient structure was prepared, achieving good one-way wet-guided and dry performance.

CN119587270AInactive Publication Date: 2025-03-11ANHUI DEEP BREATH TEXTILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411768576.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional care core material dissolves polyvinyl alcohol nanofiber during the moisture absorption process, resulting in structural instability, affecting water absorption capacity and retaining performance.

Method used

Cellulose acetate nanofiber membrane is laminated and bonded with modified polyvinyl alcohol nanofiber membrane, and an esterification reaction is used to form an ester bond that is insoluble in water, improving water solubility resistance, and a dry and breathable care core material is prepared through electrospinning and hot press lamination.

Benefits of technology

The significant fast-drying and wet-guiding gradient structure of the care core material is realized, keeping the porous wet-guiding layer dry and in contact with the skin, giving the care core material good one-way wet and dry performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a production process of a dry and breathable nursing core material, and belongs to the technical field of preparation of nursing core materials, the production process comprises the following steps: step S1, preparation of cellulose acetate nanofibers; s2, pressing the cellulose acetate nanofiber membrane and the modified polyvinyl alcohol nanofiber membrane to obtain a composite nanofiber membrane; s3, TPU hot melt mesh glue is laid on the single face of the blended fabric, then the blended fabric and the high-water-absorption face of the composite nanofiber membrane are pressed at the temperature of 150-160 DEG C, and the dry and breathable nursing core material is obtained; the nursing core material with the first layer being the porous moisture conduction layer, the second layer being the high moisture absorption layer and the third layer being the waterproof breathable layer has a remarkable quick-drying moisture conduction gradient structure, liquid molecules can be quickly transmitted to the high moisture absorption layer through multiple holes of the grooves under the moisture conduction gradient effect, and the porous moisture conduction layer is kept dry when making contact with the skin; the nursing core material is endowed with good one-way moisture conduction and dry and comfortable performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nursing core material preparation, and specifically relates to a dry and breathable nursing core material and a production process thereof. Background Art

[0002] As people's awareness of personal health care increases, consumers pay more and more attention to the quality of care products. Traditional care products often have problems such as poor air permeability of the core material and insufficient dryness, which causes users to feel damp and uncomfortable during wearing.

[0003] In the prior art, polyvinyl alcohol nanofibers are usually used as hygroscopic materials when preparing care core materials. Polyvinyl alcohol has strong hygroscopic properties. It can quickly absorb liquid molecules and lock in liquids, giving the care core materials good hygroscopic properties. However, the polyvinyl alcohol nanofibers will be dissolved during the hygroscopic process, causing the structure of the care core material to become unstable, affecting its water absorption capacity and retention performance, and limiting its application in the hygroscopic performance of care core materials. Therefore, how to improve the dissolution phenomenon of polyvinyl alcohol nanofibers during the hygroscopic process of the care core material is a technical problem that needs to be solved at present. Summary of the invention

[0004] The object of the present invention is to provide a dry and breathable care core material and a production process thereof to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A production process of a dry and breathable care core material comprises the following steps:

[0007] Step S1, adding cellulose acetate powder to a mixed solution of N,N-dimethylacetamide and acetone, dissolving by ultrasonication and then performing electrostatic spinning to obtain a cellulose acetate nanofiber membrane;

[0008] Step S2, placing the cellulose acetate nanofiber membrane and the modified polyvinyl alcohol nanofiber membrane face to face, and then performing pad lamination at a high temperature of 110-120° C. for 30-35 seconds to obtain a composite nanofiber membrane;

[0009] Step S3, lay TPU hot melt web adhesive on one side of the blended fabric, and then laminate it with the highly water-absorbent side of the composite nanofiber membrane, and hot-press laminate for 20-25 seconds at a temperature of 150-160°C and a lamination pressure of 0.5MPa to obtain a dry and breathable care core material.

[0010] Furthermore, in step S1, the dosage ratio of the mixed solution of N,N-dimethylacetamide and acetone to the cellulose acetate powder is 60 mL:5.1-7.2 g; and the volume ratio of N,N-dimethylacetamide to acetone in the mixed solution of N,N-dimethylacetamide and acetone is 1:1.5-2.

[0011] Furthermore, the electrospinning has a spinning voltage of 16-18 kV, a spinning distance of 16-18 cm, and a spinning flow rate of 2.3-2.5 mL / h.

[0012] The modified polyvinyl alcohol nanofiber membrane of the present invention has high hydrophilicity and strong water retention capacity, which can make the skin feel damp and cold. Therefore, porous acetate nanocellulose is used as a raw material, and a cellulose acetate nanofiber membrane with a porous surface having grooves is obtained by electrospinning. The cellulose acetate nanofiber membrane can be laminated and connected through an esterification reaction between the acetyl group and the hydroxyl group on the surface of the modified polyvinyl alcohol nanofiber membrane, and the peel strength of the composite nanofiber membrane is improved through intermolecular forces, so that a firmly bonded composite nanofiber membrane is obtained. Since the surface of the cellulose acetate nanofiber membrane presents a porous structure with grooves, its specific surface area and capillary effect are increased, and it has a significant moisture conduction gradient, which can keep the skin dry when in contact.

[0013] Furthermore, in step S2, the usage ratio of the cellulose acetate nanofiber membrane and the modified polyvinyl alcohol nanofiber membrane is 3-5g:6-8g.

[0014] Furthermore, the modified polyvinyl alcohol nanofiber membrane is prepared by the following steps:

[0015] Add polyvinyl alcohol to deionized water, stir to dissolve, add sodium dodecylbenzene sulfonate aqueous solution, stir and mix at 90-95°C, add polyacrylic acid, continue stirring to react for 8-10 hours, let stand to degas, and then perform electrospinning at a spinning voltage of 18-19 kV, a spinning distance of 17-18 cm, and a spinning flow rate of 0.8-1 mL / h to obtain a modified polyvinyl alcohol nanofiber membrane.

[0016] The present invention uses sodium dodecylbenzene sulfonate as a surfactant, and forms a water-insoluble ester bond by esterifying the carboxyl group of polyacrylic acid and the hydroxyl group of polyvinyl alcohol at high temperature, thereby improving the water solubility of the modified polyvinyl alcohol, so that the modified polyvinyl alcohol nanofiber membrane has high water absorption performance and will not be dissolved.

[0017] Furthermore, the usage ratio of the deionized water, polyvinyl alcohol, sodium dodecylbenzene sulfonate aqueous solution and polyacrylic acid is 60 mL: 6.3-8.4 g: 8 mL: 2.9-4.8 g; and the concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.1-0.2 wt %.

[0018] Furthermore, in step S3, the usage ratio of the blended fabric, TPU hot melt web adhesive, and composite nanofiber membrane is 5.8g:0.2-0.3g:3.2g.

[0019] Furthermore, the highly water-absorbent side of the composite nanofiber membrane is a modified polyethanol nanofiber membrane surface.

[0020] Furthermore, the blended fabric is made by weaving bamboo charcoal fiber as warp yarn and honeycomb microporous polyester fiber as weft yarn at a mass ratio of 3:7-8.

[0021] A dry and breathable care core material includes the above production process.

[0022] Beneficial effects of the present invention:

[0023] On the one hand, the modified polyvinyl alcohol nanofiber membrane of the present invention introduces water-insoluble ester bonds through an esterification reaction with polyacrylic acid to improve its water resistance. On the other hand, when laminated and bonded with cellulose acetate nanofiber membrane, it can also undergo an esterification reaction with it to form an ester group, effectively avoiding the water solubility of the modified polyvinyl alcohol nanofiber membrane during the moisture absorption process.

[0024] The present invention uses a cellulose acetate nanofiber membrane with grooves and pores as the first layer, and laminates and bonds it with a modified polyvinyl alcohol nanofiber membrane through intermolecular forces to obtain a nanocomposite nanofiber membrane with a moisture conduction gradient structure, and then hot-presses and bonds it with a blended fabric woven from waterproof and breathable honeycomb microporous polyester fibers and bamboo charcoal fibers to obtain a care core material with a first layer of a porous moisture conduction layer, a second layer of a high moisture absorption layer, and a third layer of a waterproof and breathable layer. The care core material has a significant quick-drying moisture conduction gradient structure. When encountering liquids such as water, the liquid molecules can be quickly transferred to the high moisture absorption layer through the grooves and pores under the action of the moisture conduction gradient, keeping the porous moisture conduction layer dry in contact with the skin, and giving the care core material good unidirectional moisture conduction and drying properties. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] This embodiment provides a modified polyvinyl alcohol nanofiber membrane, which is prepared by the following steps:

[0028] Add 6.3 g of polyvinyl alcohol to 60 mL of deionized water, stir to dissolve, add 8 mL of 0.1 wt% sodium dodecylbenzene sulfonate aqueous solution, stir to mix at 90 ° C, add 2.9 g of polyacrylic acid, continue to stir and react for 8 hours, let stand to degas, and then perform electrospinning at a spinning voltage of 18 kV, a spinning distance of 17 cm, and a spinning flow rate of 0.8 mL / h to obtain a modified polyvinyl alcohol nanofiber membrane.

[0029] Example 2

[0030] This embodiment provides a modified polyvinyl alcohol nanofiber membrane, which is prepared by the following steps:

[0031] Add 7.3 g of polyvinyl alcohol to 60 mL of deionized water, stir to dissolve, add 8 mL of 0.15 wt% sodium dodecylbenzene sulfonate aqueous solution, stir to mix at 93 ° C, add 3.2 g of polyacrylic acid, continue to stir and react for 9 hours, let it stand to degas, and then perform electrospinning at a spinning voltage of 18 kV, a spinning distance of 17 cm, and a spinning flow rate of 0.9 mL / h to obtain a modified polyvinyl alcohol nanofiber membrane.

[0032] Example 3

[0033] This embodiment provides a modified polyvinyl alcohol nanofiber membrane, which is prepared by the following steps:

[0034] Add 8.4 g of polyvinyl alcohol to 60 mL of deionized water, stir to dissolve, add 8 mL of 0.2 wt% sodium dodecylbenzene sulfonate aqueous solution, stir to mix at 95 ° C, then add 4.8 g of polyacrylic acid, continue to stir and react for 10 hours, let it stand for degassing, and then perform electrospinning at a spinning voltage of 19 kV, a spinning distance of 18 cm, and a spinning flow rate of 1 mL / h to obtain a modified polyvinyl alcohol nanofiber membrane.

[0035] Comparative Example 1

[0036] Compared with Example 1, the difference is that an equal amount of polyacrylic acid is replaced by polyvinyl pyrrolidone, and the other raw materials and steps are the same.

[0037] Example 4

[0038] This embodiment provides a production process for a dry and breathable care core material, comprising the following steps:

[0039] Step S1, adding 5.1 g of cellulose acetate powder to a mixed solution prepared by 60 mL of N,N-dimethylacetamide and acetone in a volume ratio of 1:1.5, dissolving by ultrasonication, and then electrospinning at a spinning voltage of 16 kV, a spinning distance of 16 cm, and a spinning flow rate of 2.3 mL / h to obtain a cellulose acetate nanofiber membrane;

[0040] Step S2, 3 g of cellulose acetate nanofiber membrane and 6 g of modified polyvinyl alcohol nanofiber membrane prepared in Example 1 are laminated face to face, and then pad-laminated at a high temperature of 110° C. for 30 seconds to obtain a composite nanofiber membrane;

[0041] Step S3, using bamboo charcoal fiber as warp yarn and honeycomb microporous polyester fiber as weft yarn, weaving warp and weft in a mass ratio of 3:7 to obtain a blended fabric;

[0042] Step S4: lay 0.2g of TPU hot-melt web adhesive on one side of 5.8g of blended fabric, and then laminate it with the high water absorption side of 3.2g of composite nanofiber membrane, and hot-press laminate for 20s at a temperature of 150°C and a lamination pressure of 0.5MPa to obtain a dry and breathable care core material.

[0043] Example 5

[0044] This embodiment provides a production process of a dry and breathable care core material, comprising the following steps:

[0045] Step S1, adding 6.2 g of cellulose acetate powder to a mixed solution prepared by 60 mL of N,N-dimethylacetamide and acetone in a volume ratio of 1:1.8, dissolving by ultrasonication, and then electrospinning at a spinning voltage of 17 kV, a spinning distance of 17 cm, and a spinning flow rate of 2.4 mL / h to obtain a cellulose acetate nanofiber membrane;

[0046] Step S2, 4 g of cellulose acetate nanofiber membrane and 7 g of modified polyvinyl alcohol nanofiber membrane prepared in Example 2 are laminated face to face, and then pad-laminated at a high temperature of 115° C. for 33 seconds to obtain a composite nanofiber membrane;

[0047] Step S3, using bamboo charcoal fiber as warp yarn and honeycomb microporous polyester fiber as weft yarn, weaving warp and weft in a mass ratio of 3:7 to obtain a blended fabric;

[0048] Step S4, lay 0.25g TPU hot melt web adhesive on one side of 6.0g blended fabric, and then laminate it with the high water absorption side of 4.0g composite nanofiber membrane, and hot press laminate for 23s at a temperature of 155°C and a lamination pressure of 0.5MPa to obtain a dry and breathable care core material.

[0049] Example 6

[0050] This embodiment provides a production process of a dry and breathable care core material, comprising the following steps:

[0051] Step S1, adding 7.2 g of cellulose acetate powder to a mixed solution prepared by 60 mL of N,N-dimethylacetamide and acetone in a volume ratio of 1:2, dissolving by ultrasonication, and then electrospinning at a spinning voltage of 18 kV, a spinning distance of 18 cm, and a spinning flow rate of 2.5 mL / h to obtain a cellulose acetate nanofiber membrane;

[0052] Step S2, 5 g of cellulose acetate nanofiber membrane and 8 g of modified polyvinyl alcohol nanofiber membrane prepared in Example 3 are laminated face to face, and then pad-laminated at a high temperature of 120° C. for 35 seconds to obtain a composite nanofiber membrane;

[0053] Step S3, using bamboo charcoal fiber as warp yarn and honeycomb microporous polyester fiber as weft yarn, weaving warp and weft in a mass ratio of 3:7-8 to obtain a blended fabric;

[0054] Step S4, lay 0.3g TPU hot melt web adhesive on one side of 6.2g blended fabric, and then laminate it with the high water absorption side of 4.6g composite nanofiber membrane, and hot press laminate for 25s at a temperature of 160°C and a lamination pressure of 0.5MPa to obtain a dry and breathable care core material.

[0055] Comparative Example 2

[0056] Compared with Example 4, the difference is that the modified polyvinyl alcohol nanofiber membrane prepared in Comparative Example 1 is used, and the other raw materials and steps are the same.

[0057] Comparative Example 3

[0058] Compared with Example 4, the difference is that the cellulose acetate nanofiber membrane is replaced by an equal amount of polyamide nanofiber membrane, and the other raw materials and steps are the same.

[0059] Comparative Example 4

[0060] Compared with Example 4, the difference is that the blended fabric is replaced by polyester fabric in equal amount, and the other raw materials and steps are the same.

[0061] Performance tests were performed on Examples 4 to 6 and Comparative Examples 1 to 3. Quick-drying test: the sample was made into a 10 cm × 10 cm specimen, 5 mL of water was dropped on the surface of the specimen, and the surface of the core material was touched after 6 seconds to see if it was dry. Air permeability test: referring to GB / T 5453-1997, the air permeability tester YG461 E was used to test the air permeability of the sample, and the air permeability was calculated and recorded. The specimen size was 20 cm 2; Moisture absorption performance test: refer to GB / T 21655.1-2008, the results are shown in Table 1:

[0062] Table 1

[0063] project Example 4 Example 5 Example 6 Comparative Example 2 Comparative Example 3 Comparative Example 4 Dryness Dry Dry Dry Dry Dampness Dry Air permeability (mm / s) 256.8 234.9 291.3 225.4 215.9 191.2 Wicking height / mm 156 162 171 121 142 149

[0064] It can be seen from Table 1 that the air permeability and wicking height of the care core materials made of cellulose acetate nanofiber membrane and modified polyvinyl alcohol nanofiber membrane in Examples 4-6 are greater than those in Comparative Examples 2-4, and have good moisture absorption and air permeability. In addition, compared with Comparative Examples 2 and 3, Example 4 not only has high air permeability, but also has good moisture absorption and quick-drying properties. Therefore, the care core material made of cellulose acetate nanofiber membrane, modified polyvinyl alcohol nanofiber membrane and blended fabric has better dry and breathable performance.

[0065] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process for a dry and breathable care core material, characterized in that: The following steps are involved: Step S1, adding cellulose acetate powder to a mixed solution of N,N-dimethylacetamide and acetone, dissolving by ultrasonication and then performing electrostatic spinning to obtain a cellulose acetate nanofiber membrane; Step S2, placing the cellulose acetate nanofiber membrane and the modified polyvinyl alcohol nanofiber membrane face to face, and then performing pad lamination at 110-120° C. for 30-35 seconds to obtain a composite nanofiber membrane; Step S3, lay TPU hot melt web adhesive on one side of the blended fabric, and then laminate it with the highly water-absorbent side of the composite nanofiber membrane, and hot-press laminate for 20-25 seconds at a temperature of 150-160°C and a lamination pressure of 0.5MPa to obtain a dry and breathable care core material.

2. The production process of a dry and breathable care core material according to claim 1, characterized in that: In step S1, the dosage ratio of the mixed solution of N,N-dimethylacetamide and acetone to the cellulose acetate powder is 60 mL: 5.1-7.2 g; the volume ratio of N,N-dimethylacetamide to acetone in the mixed solution of N,N-dimethylacetamide and acetone is 1: 1.5-2.

3. The production process of a dry and breathable care core material according to claim 1, characterized in that: The electrospinning has a spinning voltage of 16-18 kV, a spinning distance of 16-18 cm, and a spinning flow rate of 2.3-2.5 mL / h.

4. The production process of a dry and breathable care core material according to claim 1, characterized in that: In step S2, the usage ratio of the cellulose acetate nanofiber membrane and the modified polyvinyl alcohol nanofiber membrane is 3-5g:6-8g.

5. The production process of a dry and breathable care core material according to claim 1, characterized in that: The modified polyvinyl alcohol nanofiber membrane is prepared by the following steps: Add polyvinyl alcohol to deionized water, stir to dissolve, add sodium dodecylbenzene sulfonate aqueous solution, stir and mix at 90-95°C, add polyacrylic acid, continue stirring to react for 8-10 hours, let stand to degas, and then perform electrospinning at a spinning voltage of 18-19 kV, a spinning distance of 17-18 cm, and a spinning flow rate of 0.8-1 mL / h to obtain a modified polyvinyl alcohol nanofiber membrane.

6. The production process of a dry and breathable care core material according to claim 5, characterized in that: The usage ratio of the deionized water, polyvinyl alcohol, sodium dodecylbenzene sulfonate aqueous solution and polyacrylic acid is 60 mL: 6.3-8.4 g: 8 mL: 2.9-4.8 g; the concentration of the sodium dodecylbenzene sulfonate aqueous solution is 0.1-0.2 wt %.

7. The production process of a dry and breathable care core material according to claim 1, characterized in that: The usage ratio of the blended fabric, TPU hot melt web adhesive and composite nanofiber membrane in step S3 is 5.8g:0.2-0.3g:3.2g.

8. The production process of a dry and breathable care core material according to claim 1, characterized in that: The highly water-absorbent side of the composite nanofiber membrane is a modified polyethanol nanofiber membrane surface.

9. The production process of a dry and breathable care core material according to claim 1, characterized in that: The blended fabric is prepared by weaving bamboo charcoal fibers as warp yarns and honeycomb microporous polyester fibers as weft yarns at a mass ratio of 3:7-8.

10. A dry and breathable care core material, characterized in that: Prepared according to the production process according to any one of claims 1 to 9.